2020
DOI: 10.1021/acsanm.0c00130
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Combs as Antiadhesive Tools to Manipulate Nanofibers

Abstract: Nanofibrous multifunctional materials have attracted a lot of attention because of the benefits of their special structure. Despite the diverse benefits of nanofibrous materials, their inherent stickiness to any surface is a major obstacle in producing and processing such materials. There are many paragons in which biological models or elements from nature have been biomimetically adapted in various areas in order to resolve technical problems, such as the silent flight of the owl, the lotus effect, or the sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 26 publications
2
47
0
Order By: Relevance
“…Other applications and of LIPSS that are currently explored are: Biomimetic surfaces: Nature provides many highly optimized surface functionalities that may be transferred to technical applications via tailored laser-processing, including LIPSS. Examples are dirt-repellent surfaces through the well-known lotus effect, anti-icing [ 57 , 58 ], the directional transport of liquids inspired by moisture-harvesting lizards [ 59 ] and bark bugs [ 60 ], antiadhesive surfaces inspired by cribellating spiders [ 61 ], or antibacterial [ 62 , 63 , 64 , 65 , 66 , 67 ], cell-repellent [ 68 ], and cell-stimulating/-adapting surfaces [ 69 , 70 , 71 ] for medical applications [ 72 ]. A detailed review of the laser engineering of biomimetic surfaces is provided in [ 6 ].…”
Section: Recent (Ongoing) Trendsmentioning
confidence: 99%
“…Other applications and of LIPSS that are currently explored are: Biomimetic surfaces: Nature provides many highly optimized surface functionalities that may be transferred to technical applications via tailored laser-processing, including LIPSS. Examples are dirt-repellent surfaces through the well-known lotus effect, anti-icing [ 57 , 58 ], the directional transport of liquids inspired by moisture-harvesting lizards [ 59 ] and bark bugs [ 60 ], antiadhesive surfaces inspired by cribellating spiders [ 61 ], or antibacterial [ 62 , 63 , 64 , 65 , 66 , 67 ], cell-repellent [ 68 ], and cell-stimulating/-adapting surfaces [ 69 , 70 , 71 ] for medical applications [ 72 ]. A detailed review of the laser engineering of biomimetic surfaces is provided in [ 6 ].…”
Section: Recent (Ongoing) Trendsmentioning
confidence: 99%
“…The calamistrum is not necessary for the extraction of the nanofibers themselves, but thread structure differs largely between combed and uncombed threads [15,20]. Despite the direct contact with the nanofibers during combing, the calamistrum remains free of fiber residues [21,22]. Correct contact seems essential for the functionality of the calamistrum [23].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the specific shape of the bacteria plays a decisive role for their adhesion as well as the depth-to-period aspect ratio of laser-generated microstructures. While recent publications highlight the anti-biofouling capacities of bioinspired surface structures [38,39] mimicking plant leaves [40], shark and gecko skin [41][42][43] or insect wings [44][45][46], Joel and co-workers demonstrated antiadhesive properties of a nanotextured surface structure bioinspired by cribellate spiders [47]. Here, investigated nanofibers had similar fiber-diameters as bacterial flagella and pili [48], thus, suggesting nano-ripples as a promising strategy to combat nanofiber-mediated bacterial adhesion.…”
Section: Introductionmentioning
confidence: 73%
“…These findings are in accordance with previous studies on cribellate spider silk nanofiber adhesion on laser structured PET foils. Joel et al demonstrated that PET foils structured with LIPSS with spatial periods of approximately 320-340 nm reduced the adhesion forces of nanofibers with a comparable diameter of F pili (10-30 nm for the spider silk [47] vs. ~8-9 nm for the pili [48], respectively).…”
Section: Mainly Affect the Nanofiber-mediated Adhesionmentioning
confidence: 99%